2010
DOI: 10.1021/jp910315e
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics between Poly(ethylene glycol) and Hydrophilic Modified Ibuprofen in Aqueous Solution

Abstract: The solubility of ibuprofen, a nonsteroidal anti-inflammatory drug (NSAID), is enhanced by synthesizing ibuprofen ester with a water-soluble polymer, poly(ethylene glycol) (PEG), and the product obtained functions as a nonionic surfactant (IBF-PEG800, IP800). The morphology and aggregation behavior of IP800 micelles and IP800/PEG complexes in aqueous solution are investigated by (1)H NMR technology, dynamic light scattering (DLS), isothermal titration calorimetry (ITC), and fluorescence resonance energy transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…A similar increase and then decrease in micelle size with increasing temperature has recently been reported for Pluronic L44 by Naskar et al They attributed the decrease to the transition of larger to smaller aggregates. Wei et al reported a similar size variation just above the CMC of a synthesized surfactant (ibuprofen–poly(ethylene glycol)). For our samples, this behavior is also observed for cases involving the addition of PEO.…”
Section: Results and Discussionmentioning
confidence: 79%
“…A similar increase and then decrease in micelle size with increasing temperature has recently been reported for Pluronic L44 by Naskar et al They attributed the decrease to the transition of larger to smaller aggregates. Wei et al reported a similar size variation just above the CMC of a synthesized surfactant (ibuprofen–poly(ethylene glycol)). For our samples, this behavior is also observed for cases involving the addition of PEO.…”
Section: Results and Discussionmentioning
confidence: 79%
“…With increasing weight ratios of PEGDA to NIPAm, the LCSTs of the hydrogels increased at the corresponding molecular weight of PEGDA. Except for the 1:0.25PEG(508) and 1:0.5PEG(508) hydrogels that were synthesized from liquid PEGDA (Mn = 508), the LCSTs at Mn = 3400, 6000, 10,000 and 20,000 with the same co-monomer ratio decreased with an increase in the molecular weight as a consequence of decreased number of hydrophilic oxyethylene groups [39]. Furthermore, at the same weight ratio of PEGDA, increasing the molecular weight of PEGDA decreased a molar percentage of PEGDA, and, as a result, decreased the crosslinking density of the hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology and aggregation behavior of IP800 micelles and IP800/PEG complexes in aqueous solution have been investigated by 1 H NMR, DLS, ITC, and fluorescence resonance energy transfer (FRET) experiments. 138 Micelles formed by block copolymers of Methoxy PEG (MPEG)-b-poly(e-caprolactone) bearing ketone groups (P(CL-co-OPD)) have been proposed as carriers for doxorubicin, a representative anticancer drug. Their 1 H NMR spectra indicate that the polymers form micelles exposing hydrophilic segments to the aqueous environments.…”
Section: Micelles In Amphiphile-solvent Systemsmentioning
confidence: 99%